A novel low-dielectric nanocomposite with hydrophobicity property: Fluorinated MOFs modified bismaleimide-triazine resin. (December 2021) - Li, Xiaodan; Liu, Xiaoqing; Hu, Xinyu; He, Rui; Liu, Hongyu
Abstract: A fluorine-functionalized zirconium-based metal organic framework (F4 -UiO-66) was successfully synthesized via the reflux method, and the F4 -UiO-66/BT nanocomposites of F4 -UiO-66 modified bismaleimide-triazine resin (BT resin) were prepared. The effects of F4 -UiO-66 on the crosslinking structure and properties of BT resin were evaluated for the first time. The investigations showed that the active H in F4 -UiO-66 effectively catalyzed the self-polymerization of cyanate ester and promoted the formation of more rigid triazine rings which increased the initial storage modulus of nanocomposites. But the steric hindrance effect of F4 -UiO-66 reduced the crosslinking density, which increased the free volume of nanocomposites. So, the dielectric constants of the nanocomposites were significantly reduced with the increase of F4 -UiO-66 for the reduction of molecular polarization due to triazine rings and C–F bonds, and the decrease of polarization density caused by the nanopores and free volume. In addition, F4 -UiO-66 was evenly dispersed in BT resin. On the basis of maintaining the thermal stability, the toughness and hydrophobic properties of nanocomposites were also enhanced. This study provided a novel approach for low-dielectric materials with hydrophobic property through the synergy between the nanopores and the C–F bonds. Graphical Abstract: ga1